Closed-loop stimulation of the pelvic nerve for optimal micturition. (25th September 2018) - Peh, Wendy Yen Xian; Raczkowska, Marlena N; Teh, Yuni; Alam, Monzurul; Thakor, Nitish V; Yen, Shih-Cheng
Abstract: Objective . Neural stimulation to restore bladder function has traditionally relied on open-loop approaches that used pre-set parameters, which do not adapt to suboptimal outcomes. The goal of this study was to examine the effectiveness of a novel closed-loop stimulation paradigm for improving micturition or bladder voiding. Approach . We compared the voiding efficiency obtained with this closed-loop framework against open-loop stimulation paradigms in anesthetized rats. The bladder pressures that preceded voiding, and the minimum current amplitudes for stimulating the pelvic nerves to evoke bladder contractions, were first calibrated for each animal. An automated closed-loop system was used to initiate voiding upon bladder fullness, adapt the stimulation current by using real-time bladder pressure changes to classify voiding outcomes, and halt stimulation when the bladder had been emptied or when the safe stimulation limit was reached. Main results. In vivo testing demonstrated that the closed-loop system achieved high voiding efficiency or VE (75.7% ± 3.07%, mean ± standard error of the mean) and outperformed open-loop systems with either conserved number of stimulation epochs (63.2% ± 4.90% VE) or conserved charge injected (32.0% ± 1.70% VE). Post-hoc analyses suggest that the classification algorithm can be further improved with data from additional closed-loop experiments. Significance . This novel approach may be applied to an implantable device for treating underactive bladder (<60% VE), especially in cases where under- or over-stimulation of the nerve is a concern.